PENERAPAN PEMBELAJARAN LANGSUNG DALAM MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS IV SD - Nur Safitri (CV. ADIBA ASIHA AMIRA, 2026)
This study aims to determine the application of direct instruction in improving the understanding of mathematical concepts among fourth-grade elementary school students. The background of this study is the low level of students' understanding of mathematical concepts, so an appropriate learning method is needed to help students understand the material better. The research method used is library research by utilizing various sources from books, scientific journals, and relevant information from the internet. Data were collected through literature studies and analyzed descriptively to obtain a deeper understanding of the application of direct instruction. The results of the study show that direct instruction can help students understand mathematical concepts in a gradual and systematic way, as the teacher provides clear explanations, examples, and structured exercises. This method can improve students' conceptual understanding and help them solve problems more effectively. In conclusion, direct instruction is an effective method to improve the understanding of mathematical concepts among fourth-grade elementary school students. Therefore, teachers are encouraged to apply this method in the learning process.